A Patient-centered Hospital in Malaysia in Accordance with Maqasid Syariah Principles: A Comprehensive Review and Prospective Research Directions - Ahmad Luqmanulhakim Sunawari; Azira Khalil; Madihah Mat Idris; Azlina Mokhtar (Department of Theology and Philosophy Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2024)
Indexed by Scopus/ERA/MyCite